2000
DOI: 10.1029/1999jd900414
|View full text |Cite
|
Sign up to set email alerts
|

Regional aerosol distribution and its long‐range transport over the Indian Ocean

Abstract: Abstract. Aerosol chemical, microphysical, and optical data collected from an island station and a ship during the first field phase of the Indian Ocean Experiment provided a unique opportunity to develop models for retrieving aerosol optical depth from the advanced very high resolution radiometer (AVHRR) onboard NOAA14 during JanuaryMarch 1998. Columnar aerosol optical depth (AOD) over Arabian Sea, Bay of Bengal, and Indian Ocean was derived for the 630 nm wavelength from the radiance in channel 1 (580-680 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
99
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(105 citation statements)
references
References 33 publications
4
99
1
1
Order By: Relevance
“…Several studies have documented that aerosol concentration over the South Asian region progressively builds up during the dry season (October-April; e.g., Rajeev and Ramanathan 2002). The October-May distribution of the AI over the Indian Subcontinent reveals that the Indo-Gangetic plain is one of the areas with high loading of aerosols, the other areas being the Arabian Peninsula and the Taklamakan Desert.…”
Section: Toms Aerosol Index Variability Over the Indian Subcontinentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have documented that aerosol concentration over the South Asian region progressively builds up during the dry season (October-April; e.g., Rajeev and Ramanathan 2002). The October-May distribution of the AI over the Indian Subcontinent reveals that the Indo-Gangetic plain is one of the areas with high loading of aerosols, the other areas being the Arabian Peninsula and the Taklamakan Desert.…”
Section: Toms Aerosol Index Variability Over the Indian Subcontinentmentioning
confidence: 99%
“…The Indian Ocean Experiment (INDOEX) revealed that a 3-km-thick brownish haze layer, composed of anthropogenic [up to 75% of the average aerosol optical depth (AOD)] (Lelieveld et al 2001) and natural aerosols, is spread over most of the tropical Indian Ocean toward the Himalayan region (Ramana et al 2004) and extends over Southeast Asia into the western Pacific (e.g., Rajeev et al 2000). INDOEX documented the persistence of the brown cloud for several months from winter to spring, its large black carbon (BC) content (up to 10%-14% of the total aerosol mass), and the large perturbation to the radiative energy budget of the region (up to Ϫ25 W m Ϫ2 in the mean clear-sky radiation at the surface).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that the pollution plume generally resulted from the mixing of air masses transported over long distances and whose aerosol characteristics were quite diverse (Rajeev et al, 2000;Lobert et al, 2002). Minvielle et al (2004a, b) have shown that the regional transport model could account for the long range transport and horizontal mixing.…”
Section: Introductionmentioning
confidence: 99%
“…During the Asian winter monsoon period, the northeasterly winds from the land areas transport large amounts of continental aerosols over the oceanic regions [Rajeev et al, 2000]. This provides a unique opportunity to study the extent of transport of continental aerosols and their radiative impact over the otherwise pristine ocean areas.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of the derived AOD to surface reflectivity and aerosol single scattering albedo is shown by Rajeev et al [2000]. Figure 2 shows sensitivity of the derived AOD to the aerosol single scattering albedo (to), which is found to be the largest source of uncertainty.…”
Section: Introductionmentioning
confidence: 99%